Policies to Achieve Discrimination on the Effective Price of Heroin - Moore, Mark H. (American Economic Review, 1973)
A. The Effective Price of Heroin Traditional representations of demand curves assume that the dollar price of a good is the only significant element of the cost to the consuming individual. For most goods, other aspects of consumption such as transaction costs and uncertainty about quality are assumed to play a minor role. Not so with heroin. Heroin is different because, first, users face significant transaction costs. Often they must search intently for an opportunity to score. In addition, in any attempt to score they risk being arrested or victimized by other addicts. The consequences of these transaction costs include withdrawal symptoms, beatings, and jail. Second, users face quality uncertainties which may be even more significant. The amount of pure heroin and the toxicity of adulterants vary widely among street bags. The possible consequences include fraud and death. Against these possible consequences of purchasing and using heroin, the dollar price may be relatively unimportant.Consequently, in describing the cost of consuming heroin, it is best to speak in terms of an effective price of heroin. The eff ective price is defined as an index including the following elements: dollar price, amount of pure heroin, toxicity of adulterants, access time, and threats of victimization and arrest. Many of these elements are uncertain quantities from the point of view of the consumer.